FAKTOR–FAKTOR YANG MEMPENGARUHI KECENDERUNGAN MELAKUKAN FRAUD : ANALISIS PERSEPSI ASN KABUPATEN INDRAGIRI HULU - Haeru Purwanto; Rita Anugerah; Rasuli Rasuli (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
This study aims to determine the effect of the pressure, opportunity, rationalization and capability factors on fraud in the government sector. The population in this study were all civil servants who worked in Regional Device Organizations in Indragiri Hulu Regency, totaling 32. The author took a sample of 5 people in each organization. Samples taken consist of Budget Users / Budget User Proxies, Finance subdivision heads, Financial Management Officials, Expenditures Treasurers, Treasurers and Goods Treasurers. The data analysis technique used in this study is a Structural Equation Modeling analysis technique.The results of this research are that pressure, opportunity and capability have a positive and significant effect on fraud in the government sector of Indragiri Hulu Regency. While rationalization has a negative and significant effect on fraud in the government sector of Indragiri Hulu Regency. There are still weaknesses in the use of internal control systems due to limited information and time, due to environmental pressure, or due to limited ability; collusion or negative collaboration of a group of people and intentional violations by superiors. Often the occurrence of unethical behavior in the form of the use of official vehicles for personal use, there are officials who use positions to request more facilities than partners / partners outside the applicable provisions and the attitude of omitting employees when other employees act detrimentally in the environment where they work.